Alvin Hansen and the Fiscal Policy Seminar - Salant, Walter S. (Quarterly Journal of Economics, 1976)
Journal Article Alvin Hansen and the Fiscal Policy Seminar Get access Walter S. Salant Walter S. Salant Brookings Institution Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 90, Issue 1, February 1976, Pages 14–23, https://doi.org/10.2307/1886082 Published: 01 February 1976